Energy–exergy analysis for performance improvement of Brayton–Rankine combined cycle system by utilizing a solar absorption refrigeration cycle (case study: Kahnuj Combined Cycle Power Plant) - Moslem Esfandiari; Fathollah Pourfayaz; Alibakhsh Kasaeian; Ali Gholami (Energy Science & Engineering, 2024)
Abstract Gas–steam combined cycle power plants are the most efficient electricity‐generation units based on fossil fuels. However, these power plants are prone to efficiency decrease in hot climates as high ambient temperatures adversely influence the gas turbine's output. The present study investigated the effect of incorporating a solar absorption refrigeration (SAR) system into an actual combined cycle power plant for the first time. First, the energy and exergy analyses were performed using THERMOFLOW software. Then, the influence of the ambient temperature (10°C–52.5°C) on the power plant's performance and its components was investigated. The SAR system was then used to cool the compressor's input air and improve the power generation capacity by employing TRNSYS software. The results showed that the power plant reached its maximum efficiency at an ambient temperature of 26.6°C. However, its overall efficiency and net power generation were dropped with a further increase in the ambient temperature. Employing the SAR system for each gas turbine in the power plant on a sunny day until 2 p.m. would decrease the compressor's input air temperature. For example, for the refrigeration capacities of 450, 700, and 1000 tons for each gas turbine, the temperature was reduced by nearly 3°C, 5°C, and 7°C, respectively. Under the same condition, power generation capacity improved by 12.5, 24, and 32.5 MW, and the overall efficiency rose by 0.6%, 1.4%, and 2%. Such an increase in power and efficiency occurred during peak demand, which was significant.